Characterization of the complete chloroplast genome of Betula pendula purple rain (betulaceae) - Meiqi Zhang; Yuan Gao; Xiaoyue Su; Weili Liu; Yanli Guo; Jing Jiang; Wei Ma (Mitochondrial DNA. Part B. Resources, 2023)
Betula pendula purple rain is a variety of Betula pendula that is native to Europe and has important ornamental and economic value. In this study, we sequenced the complete chloroplast genome of B. pendula purple rain. This genome had a typical quadripartite structure with 160,552 bases, including a large single copy (LSC) region of 89,433 bases, a small single copy (SCC) region of 19,007 bases and two inverted repeat (IR) regions of 26,056 bases. The GC content of the chloroplast genome was 36% and contained 124 genes, including 79 protein-coding genes, 8 rRNA genes and 37 tRNA genes. The maximum likelihood phylogenetic analysis of reported chloroplast genomes showed that B. pendula purple rain was most closely related to Betula occidentalis and Betula platyphylla.